UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE DI KELAS XI MS II SMAN PLUS PROVINSI RIAU - Hanafi, Abdul Hady Hanafi Hady; Solfitri, Titi Solfitri Titi; Yuanita, Putri Yuanita Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research based on the students’mathematics achievement at class XI MS II Senior High School Plus of Riau Province with cooperative learning Think Pair Square (TPS), there are 24 students in the class with 18 are male and 6 female. There are 20 students who achieved the passing grade by the percentage 83,3% for attitude competence. Only 10 students who achieved the pasing grade by percentage 41,6% for knowledge competence and 12 students who achieved the passing grade by the percentage 50% for skill competence for the main discussion about relevancy with algebraic operations on matrix. The research is classroom action research. This aims research to increase learning process and students’ math achievement at class VIII.2 SMPN 4 Tapungthrough the implentation cooperative learning model of structural Two Stay Two Stray.The subject of the research are 24 students from class XI MS II Senior High School Plus of Riau Province with the heterogenous level. Instrument to collect the data are observation, attitude assessment sheet, skill assessment sheet and mathematics achivement test. The observation data analyzed by using descriptive and qualitative,and for students’test by using descriptiveand quantitative. The qualitative analysis showed an improvement of learning process prior to action to the first cycle and second cycle. The results of this research showed an increase in students achievement for attitude competence from the based-score with the percentage 83,3% to 87,5% on the first cycle and 100% on the second cycle. For knowledge competence showed an increase from the based-score with the percentage 41,6% to 62,5% on the first cycle and 83,3% on the second cycle. And for skills competence showed an increase from the based-score with the percentage 50% to 62,5% on the first cycle and 87,5% on the second cycle. Based on the finding can be concluded that the implentation of cooperative learning model Think Pair Square could improve students’ mathematics achievement at class XI MS II Senior High School Plus of Riau Province in the first semester academic years 2014/2015. Key Word : Students’ Mathematics Achievement, Cooperative Learning Model of Think Pair Square, Classroom Action Research.